2016
DOI: 10.4236/health.2016.811107
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Depressive Symptoms in Female Models

Abstract: The purpose of the present study was to analyze quality of life (QoL) levels and depressive symptoms in female models in comparison to non-models. The study was conducted in Estação Saúde Gym, in Caxias do Sul, Rio Grande do Sul, Brazil. The sample of the study was composed of ten runaway and/or commercial female models between the ages of 15 and 25 from Cast One Models agency and eight control adolescent and young adult students from public/private schools and universities, all from Caxias do Sul, Rio Grande … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…However, such dissatisfaction with body weight and concerns to achieve an ideal beauty to fit in the body or professional framework are also associated with increased depressive symptoms [ 57 ]. For the mental health variable, all participants of our study presented results above the cutoff values for the Brazilian female population (> 15), corroborating previous studies that evaluated the same populations individually, which also found trend results for depressive symptoms [ 58 60 ]. In addition to the populations evaluated, there are evidences showing an increased prevalence of depressive disorders in the world population at increasingly earlier ages and twice as likely to occur in the female population [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, such dissatisfaction with body weight and concerns to achieve an ideal beauty to fit in the body or professional framework are also associated with increased depressive symptoms [ 57 ]. For the mental health variable, all participants of our study presented results above the cutoff values for the Brazilian female population (> 15), corroborating previous studies that evaluated the same populations individually, which also found trend results for depressive symptoms [ 58 60 ]. In addition to the populations evaluated, there are evidences showing an increased prevalence of depressive disorders in the world population at increasingly earlier ages and twice as likely to occur in the female population [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, such dissatisfaction with body weight and concerns to achieve an ideal beauty to t in the body or professional framework are also associated with increased depressive symptoms (49). For the mental health variable, all participants of our study presented results above the cutoff values for the Brazilian female population (>15), corroborating previous studies that evaluated the same populations individually, which also found trend results for depressive symptoms (50)(51)(52). In addition to the populations evaluated, there are evidences showing an increased prevalence of depressive disorders in the world population at increasingly earlier ages and twice as likely to occur in the female population (53).…”
Section: Discussionsupporting
confidence: 90%